Understanding women veterans' preferences for peer support interventions to promote heart healthy behaviors: A qualitative study - Karen M. Goldstein; Leah L. Zullig; Eugene Z. Oddone; Sara M. Andrews; Mary E. Grewe; Susanne Danus; Michele Heisler; Lori A. Bastian; Corrine I. Voils (Preventive Medicine Reports, 2018)
Peer support may be an effective strategy to improve heart healthy behaviors among populations who have a strong communal identity, such as women veterans. Women veterans are a particularly important group to target as they are the fastest growing sub-population within the Veterans Affairs healthcare system. Our goal was to identify aspects of peer support and modalities for providing peer support that are preferred by women veterans at risk for cardiovascular disease (CVD). In 2016, we conducted 25 semi-structured individual interviews with women veterans from the Durham VA Healthcare System aged 35–64 who were at risk of CVD, defined as presence of at least one of the following: hypertension, hyperlipidemia, obesity (BMI ≥ 30), non-insulin dependent diabetes or prediabetes, or current smoking. Interview guide design and data analysis involved conventional content analysis. Important themes for effective peer partnerships included sharing a common behavior change goal, the need for trust between peers, compatibility around level of engagement, maintaining a positive attitude, and the need for accountability. Peer support interventions may prove beneficial to address the burden of common and preventable conditions such as CVD. Among women veterans, peer support interventions should account for individual preferences in peer matching and provide opportunities for peers to engage in relationship building in-person initially through trust-building activities. Keywords: Social support, Cardiovascular disease, Veterans, Women's health